PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS POWERPOINT PADA MATERI SISTEM PERNAPASAN UNTUK SISWA SMA NEGERI 1 HILISALAWA’AHE - Halawa, Indah Yani (Universitas Nias Raya, 2024)
The purpose of this study is to provide useful, practical, and effective multimedia interactive products based on Powerpoint for the study of pernapasan systems. The current research methodology is research and development using the ADDIE paradigm. The results of interactive multimedia validation produce an average value of 96.87 and are classified as very valid. The results of the teacher's multimedia interaction practice obtained a rate-to-rate score of 3.83 in the very practical category. The results of the students' interactive multimedia training obtained a score of 3.76 in the very practical category. . And the results of the effectiveness of student motivation on student interest or attention obtained the highest results, namely 98% which was categorized as very high. Judging from the relevance aspect, the value is 98.5% and is categorized into a very high category. In terms of relevance, it also shows a figure of 98.5% which is considered very high. It is further known that the educational program aspiration level of 97.5% is considered very high; The cause of the high level of aspirational motivation is the high interest of students at SMA Negeri 1 Hilisalawa'ahe. is the motivational aspect of satisfaction as follows. In terms of relevance, it also shows a figure of 98.5% which is considered very high. It is further known that the educational program aspiration level of 97.5% is considered very high; The cause of the high level of aspirational motivation is the high interest of students at SMA Negeri 1 Hilisalawa'ahe. is the motivational aspect of satisfaction as follows. This test obtained a score of 99.2% and is classified as high. Based on the findings, interactive multimedia can motivate and improve students' learning experiences. (1) The first lesson for teachers is that they can use Powerpoint-based interactive multimedia as media during the teaching process because it can be used as a tool to increase student motivation and interest. 2) Through this multimedia, I hope that students will be able to understand the importance of teaching biology in the context of pernapasal materials. (3) For the remaining researchers, interactive multimedia based on Powerpoint can be used as a reference in pertinent studies